Insulin-Like Growth Factor I and the Pathogenesis of Delirium: A Review of Current Evidence. (3rd July 2011) - Adamis, Dimitrios; Meagher, David
Abstract : Delirium is a frequent complication in medically ill elderly patients that is associated with serious adverse outcomes including increased mortality. Delirium risk is linked to older age, dementia, and illness that involves activation of inflammatory responses. IGF-I is increasingly postulated as a key link between environmental influences on body metabolism with a range of neuronal activities and has been described as the master regulator of the connection between brain and bodily well-being. The relationships between IGF-I and ageing, cognitive impairment and inflammatory illness further support a possible role in delirium pathogenesis. Five studies of IGF-I in delirium were identified by a systematic review. These conflicting findings, with three of the five studies indicating an association between IGF-1 and delirium occurrence, may relate to the considerable methodological differences in these studies. The relevance of IGF-I and related factors to delirium pathogenesis can be clarified by future studies which account for these issues and other confounding factors. Such work can inform therapeutic trials of IGF-I and/or growth hormone administration.